Form Contracts Under Revised Article 2 - James J. White (Washington University Law Quarterly, 1997)
Consider the Arizona cases with due recognition of the fact that they are interpreting section 211(3) of the Restatement, and not Revised 2-206(a), and with the understanding that the sample consists of twenty-five cases, only seven of which come from the Arizona Supreme Court led by a powerful Justice who had a clear vision about the evils of form contracts. Understand too that most of them involve insurance disputes. Although each of these qualifications might make the Arizona experience unrepresentative, it is the best we have, and I, at least, find it instructive.
Keywords: Standardized terms of contract; Consumer protection